Anti-arthritis Activity of Methanol Extract of Peperomia pellucida in Complete Freund’s Adjuvant Induced Arthritis in Wistar Rats (Nigerian Journal of Physiological Sciences, 2024)
Piperaceae includes Peperomia pellucida. It has been eaten and used to treat illnesses. This study tested the anti-arthritis activity of a 70% methanol extract of Peperomia pellucida. A complete Freund's adjuvant-induced arthritis animal model was used. Oral distilled water (10 ml/kg) did not cause arthritis in Group 1. In groups 2-4, arthritis was induced and treated with 100, 200, and 400 mg/kg of a 70% methanol extract of Peperomia pellucida. Group 5 received oral methotrexate (0.7 mg/kg) for arthritis pain. Group 6 received distilled water (10 ml/kg) for arthritis and was untreated. All inflamed animals' paw diameters, organ-to-body weight ratio, percentage change in body weight, erythrocyte sedimentation rate, haematological indices, biochemical parameters, and superoxide dismutase enzyme activity were measured. Additionally, joint and organ histopathology were examined. The 70% methanol extract of Peperonia pellucida significantly reduced arthritis inflammation diameter (***p 0.5) compared to healthy controls. Compared to the healthy control group, animals treated with the extract had no significant change (p > 0.5) in hematological and biochemical parameters. The extract and standard drug significantly reduced the erythrocyte sedimentation rate (**p